ADMINISTRATIVE AND ORGANIZATIONAL FACTORS AFFECTING THE MOTIVATION LEVELS OF FOREIGN LANGUAGE TEACHERS - ÇİÇEK SAĞLAM, Aycan and AKBAŞ, Günday (Atlas Journal, 2020)
The aim of this study is to determine the opinions of foreign language teachers working at high schools of Konak district of the city of İzmir on administrative and organizational factors affecting their motivational levels according to certain variables. The population of the research- which was conducted via using the descriptive survey model consists of 175 teachers from 31 state high schools and 200 teachers (Native speakers are not included.) from 13 private high schools located in Konak district of the city of İzmir throughout 2014-2015 academic year. The data was gathered through ‘The Scale of Administrative and Organizational Factors Affecting Motivational Levels of Foreign Language Teachers’ developed by the researcher himself. According to the findings of research, the level of presence of motivation factors arising from central administration was found to be high. The degree of these factors motivating teachers was found above the middle level. The level of presence of the motivation factors arising from the school administration was determined at a medium level. However, the degree of motivation of teachers was evaluated high level. As a result, foreign language teachers generally see the practices of the central administration negatively, but if these practices are applied positively, teachers also evaluate the degree of motivating themselves to their work higher. Although teachers see the practices of the school administration at a medium level, they see their motivation to work higher. Accordingly, it can be said that teachers’ motivation is mostly affected by the practices of school management. Of course, it is seen that the decisions and practices of the central administration regarding foreign language education and teachers are also important. In this case, in order to increase the effectiveness of foreign language education, it will be beneficial for both the central administration and the school administrations to include teachers in the decision-making mechanism. In addition, from time to time, teachers’ opinions can be determined and arrangements can be made accordingly.